Assessing the preservation potential of successive hurricane overwash deposits in Florida, USA mangroves - Isabel Hong; Kristen M. Joyse; Jennifer S. Walker; Arielle L. Nogueira; Wynn Bryant; Kara R. Radabaugh; Donald C. Barber (Scientific Reports)
Abstract Geologic records of tropical cyclones (TCs) in low-energy, back-barrier environments are established by identifying marine sediments via their allochthonous biogeochemical signal. These records have the potential to reconstruct TC intensity and frequency through time. However, modern analog studies are needed to understand which biogeochemical indicators of overwash sediments are best preserved and how post-depositional changes may affect their preservation. Here, we examine the overwash sediments of two successive land-falling, high-intensity TCs: Hurricane Ian in 2022 and Hurricane Irma in 2017. Hurricane Ian’s overwash sediments at two mangrove sites, including one directly along (Matlacha Pass) and one other distal from (Blackwater Bay) Hurricane Ian’s path through southwest Florida, USA, were identified as a light gray very poorly to poorly sorted coarse silty sand with marine microfossils and geochemical marine signature. Hurricane Irma’s overwash sediments remained identifiable from post-Irma sediments at Blackwater Bay as a gray poorly sorted coarse silt with a marine microfossil signature but lacking a distinctive geochemical signature. The identification of overwash sediments left by TCs occurring in within five years demonstrates the high preservation potential of overwash sediments in low-energy, mangrove environments. Similar environments can be utilized to advance paleotempestology studies in southwest Florida.